Therapeutic Drug Monitoring of Antidepressant by Minimally-Invasive Techniques in Eating Disorders Patients: A Clinical Research Report with A Focus on Vortioxetine - Panariello, Fabio; Mastellari, Tomas; Gianni, Angela di; Fornasari, Francesco; Borgiani, Gianluca; Protti, Michele; Mercolini, Laura; Ronchi, Diana De; Atti, Anna Rita (Archives of Clinical and Medical Case Reports, 2021)
Objective: Therapeutic Drug Monitoring (TDM) is an evidence-based practice consistent with the assumption that pharmacological plasmatic concentrations correlate better with clinical effects than prescribed doses of the used drugs. Considering the limited efficacy of Eating Disorders (ED)’s pharmacological treatment and the high rate of adverse effects, TDM may represent a valid tool to check antidepressant drugs (AD) that are frequently prescribed in patients with ED. We aim to test the feasibility of TDM in a real-life setting and to understand the reliability of oral fluid measurements related to whole blood ones. Methods: We enrolled patients attending the ED outpatient clinic in Bologna with a Body Mass Index (BMI) < 20 or > 30 kg/m2 treated with antidepressants. We collected oral fluid samples and whole blood dried microsamples by finger puncture using VAMS (Volumetric Absorptive Microsampling) technique from patients to determineTDM. Results: Nineteen patients participated in our study. Participants were treated with Sertraline (N=5), Fluoxetine (N=6), Vortioxetine (N=4), Citalopram (N=2), Escitalopram (N=1), Fluvoxamine (N=1). Preliminary results by our pilot research report show a positive correlation between plasmatic and salivary concentrations only for Vortioxetine. Additionally, only the Vortioxetine shows a pattern of plasmatic concentrations independent from the volume of distribution at the steady-state, even though the wide range of BMI. Conclusions: Despite the small size of the sample, by considering these preliminary data, we are confident that further studies will allow us to outline that TDM may represent a valid tool to achieve a consistent clinical efficacy of AD in patients diagnosed with ED.